2015
DOI: 10.1007/s00442-015-3474-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential controls by climate and physiology over the emission rates of biogenic volatile organic compounds from mature trees in a semi-arid pine forest

Abstract: Drought has the potential to influence the emission of biogenic volatile organic compounds (BVOCs) from forests and thus affect the oxidative capacity of the atmosphere. Our understanding of these influences is limited, in part, by a lack of field observations on mature trees and the small number of BVOCs monitored. We studied 50- to 60-year-old Pinus ponderosa trees in a semi-arid forest that experience early summer drought followed by late-summer monsoon rains, and observed emissions for five BVOCs-monoterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
1
10
1
Order By: Relevance
“…Combined, these results suggest that emission rate is controlled by measured physiological and environmental factors above the −2 MPa Ψthreshold, but not below. These results contrast the findings of Eller et al (2016), who found that BVOC emissions are correlated with leaf physiology below a plant physiological threshold, namely a net CO 2 assimilation rate A<ca. 2 μmol m −2 s −1 and stomatal conductance g s <0.02 mol m −2 s −1 in the needles of mature P. ponderosa trees.…”
Section: Seasonal Patterns Of Monoterpene Emissionscontrasting
confidence: 99%
See 3 more Smart Citations
“…Combined, these results suggest that emission rate is controlled by measured physiological and environmental factors above the −2 MPa Ψthreshold, but not below. These results contrast the findings of Eller et al (2016), who found that BVOC emissions are correlated with leaf physiology below a plant physiological threshold, namely a net CO 2 assimilation rate A<ca. 2 μmol m −2 s −1 and stomatal conductance g s <0.02 mol m −2 s −1 in the needles of mature P. ponderosa trees.…”
Section: Seasonal Patterns Of Monoterpene Emissionscontrasting
confidence: 99%
“…Combined, our observations are in contrast to other studies and atmospheric models that have derived algorithms based solely on the effects of foliar monoterpene concentrations and temperature for estimating monoterpene emission rate. Our observations are consistent with empirical and modeling studies demonstrating that monoterpene emissions are not under stomatal control when averaged over longer periods of time (Harley 2013, Grote et al 2013, Eller et al 2016; g s rarely entered models of emission rate (tables 1 and 2). As noted, when Ψwas above −2 MPa, a model with T a , C i (a surrogate for A apart from g s ), needle monoterpene concentration, and experimental water treatment were necessary to explain observed emission rate variability.…”
Section: Seasonal Patterns Of Monoterpene Emissionssupporting
confidence: 90%
See 2 more Smart Citations
“…Most research on environmental sensitivity of VOC emissions has focused not on flowers but on leaf emissions by trees, and often in the context of atmospheric processes (e.g. Niinemets, 2010;Trowbridge et al, 2014;Seco et al, 2015;Eller et al, 2016). Floral VOCs could also potentially respond to abiotic conditions such as temperature, soil nutrients or soil water availability (Majetic et al, 2009;Yuan et al, 2009;Burkle and Runyon, 2016).…”
Section: Introductionmentioning
confidence: 99%